Making an IMPAKT; Improving care of Chronic Kidney Disease patients in the community through collaborative working and utilizing Information Technology. Issue 1 (27th January 2017) - Xu, Gang; Major, Rupert; Shepherd, David; Brunskill, Nigel
Abstract : Chronic kidney disease (CKD) is a serious long-term condition, which if left untreated causes significant cardiovascular sequele. It is well recognized management of modifiable risk factors, such as blood pressure (BP), can lead to improved long-term outcomes. A novel information technology (IT) solution presents a possible solution to help clinicians in the community identify and manage at risk patients more efficiently. The IMproving Patient care and Awareness of Kidney disease progression Together (IMPAKT) IT tool was used to identify patients with CKD and uncontrolled hypertension in the community. A CKD nurse utilized the tool at primary care practices to identify patients who warranted potential intervention and disseminated this information to clinical staff. Blood pressure management targets and incidence of coded CKD were used to evaluate the project. Altogether 48 practices participated in an 18 month project from April 2014, and data from 20 practices, with a total adult population of 121, 362, was available for analysis. Two full consecutive QI (Quality Improvement) audit cycles were completed. There was an increase in the mean recorded prevalence of coded CKD patients over the course of the project. Similarly, there was an increase in the percentage of patients with BP been recorded and importantly there was an accompanying significant increase in CKD patients achieving BP targets. At the end of the project an additional 345 individuals with CKD achieved better blood pressure control. This could potentially prevent 9 cardiovascular events in the CKD group, translating to a cost saving of £320, 000 for the 20 practices involved. The most significant change in clinical markers occurred during cycle 1 of the audit, the improvement was maintained throughout cycle 2 of the audit. Our results show the real-life clinical impact of a relatively simple and easy to implement QI project, to help improve outcomes in patients with CKD. This was achieved through more efficient working by targeting of high-risk groups, and improved communication between primary/secondary care. The project could be adapted for other chronic disease conditions. Despite the recorded improvements in blood pressure management, a large proportion of high-risk patients remained above ideal blood pressure, additional interventions in this area need to be explored. Through collaborative and multi-professional working and utilizing IT resources, we have shown it is possible to deliver measurable and sustainable improvements in blood pressure control for patients with CKD in a real life clinical setting.